Konseptualisasi Tartīb Al-Āyāt Dalam Al-Qur'an terhadap Teori Pendidikan Modern - Martin Daniel; Moh. Azhar (Al-Kindi, 2025)
The Qur’an was revealed gradually over time, yet the arrangement of its verses in the written mushaf is non-chronological and tauqifi, fixed by divine instruction. This structure, known as tartīb al-āyāt, not only organizes the internal discourse of the Qur’an but also embodies epistemic principles that are highly relevant to contemporary educational theory. This article aims to re-examine the concept of tartīb al-āyāt and actualize it within modern pedagogical frameworks such as constructivism, learning sequence, coherence learning, scaffolding, thematic-integrative learning, and holistic education. Employing a qualitative library-research design, the study conducts descriptive-analytical and comparative-conceptual analysis of classical works in Qur’anic sciences alongside contemporary educational literature. The findings affirm that the tauqifi and coherent nature of tartīb al-āyāt can serve as a conceptual model for structuring the sequence of learning materials, strengthening coherence between concepts, designing staged learning in line with learners’ readiness, and integrating cognitive, affective, and spiritual dimensions. Thus, tartīb al-āyāt is not only central to tafsir studies but also provides a theoretical foundation for developing curriculum and instructional practices that are more meaningful, coherent, and contextually grounded within contemporary Islamic education